Case Report: A developmental and epileptic encephalopathy 45 due to de novo variant of GABRB1 - Wang, Lu; Xu, Haiquan; Shu, Jianbo; Yan, Dandan; Li, Dong; Cai, Chunquan (Frontiers in Pediatrics, 2024)
The gamma-aminobutyric acid (GABA) variant causes developmental and epileptic encephalopathy 45 (DEE45), an autosomal dominant disorder that results in oculocortical visual impairment, reduced muscle tone, psychomotor retardation, and epilepsy. Analysis of the clinical features and genetics of DEE45 may be helpful in complementing genotype-phenotype studies.We collected peripheral blood samples from the affected children and parents and extracted genomic DNA. Whole exome sequencing (WES) was utilized to identify the underlying disease-causing variant. WES showed that the prior carried a heterozygous variant c.686C>T p.(Ala229Val) in exon 7 of the GABRB1 (NM_000812.4), and no variant was detected in either parental sample. The child has DEE45.The variant c.686C>T of the GABRB1 is a possible cause of DEE45.Gene variant analysis of the relevant family lines using WES provides effective genetic counseling for developing and regressing such patients in the clinic. However, further studies are needed to verify the pathogenic mechanism.